Crímenes de Estado: ¿un concepto válido para el derecho internacional? (2014)
There is historical evidence of thousands of criminal activities committed around the globe with the acquiescence or support of the states. This evidence has originated a debate around the conceptualization of state crimes and their consequent regime of responsibility within international law. The International Law Commission of the United Nations (ILC) has presented the most intense debate among universal scenarios on this matter. ILC discussions on a States’ responsibility codification introduced the idea of state crimes as serious breaches of an international obligation of essential importance for the maintenance of international peace and security, for safeguarding the right of self-determination of peoples, for safeguarding the human being, or for the safeguarding and preservation of the human environment. In 1998 this concept was ‘put to one side’ due to lack of consensus on its content and of the regime of responsibility that it should be granted with. Since that moment, state crimes seemed to be abandoned by international law as a legal concept. Nonetheless, after some time, certain tribunals have recurred to this concept for dealing with situations of state prompted violence. This paper presents evidence regarding the resource to the concept of state crimes by domestic tribunals in Latin-America as well as by the Inter-American Court of Human Rights. This article aims at reflecting on the validity of state crimes as a concept and on its applicability in Latin-America according to the international law.